2009
DOI: 10.1002/mus.21374
|View full text |Cite
|
Sign up to set email alerts
|

Isolated posterior femoral cutaneous neuropathy following intragluteal injection

Abstract: Isolated posterior femoral cutaneous nerve lesions are rarely encountered. Electrophysiological documentation has only been made in a few cases. In this study we evaluated a 22-year-old woman with sensory loss and pain in the lower buttock and posterior thigh after left gluteal intramuscular injection. We assessed the posterior femoral cutaneous nerve using an accepted conduction technique. The results showed a normal response on the asymptomatic side, but no response on the symptomatic side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…13 By the year 2000, a review noted that just six cases of PFCN "mononeuropathy" have been reported, 14 and isolated cases continue to be reported. 15,16 As interest in the PFCN has increased, anatomical investigations have been reported. 17,18 The anatomical investigation of 20 adult cadavers reported in 2009 focused upon the perineal branch of the PFCN.…”
Section: Discussionmentioning
confidence: 99%
“…13 By the year 2000, a review noted that just six cases of PFCN "mononeuropathy" have been reported, 14 and isolated cases continue to be reported. 15,16 As interest in the PFCN has increased, anatomical investigations have been reported. 17,18 The anatomical investigation of 20 adult cadavers reported in 2009 focused upon the perineal branch of the PFCN.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated lesions of the nerve are rare, with only six cases described, and one case documented with the nerve conduction on a 25 year old woman with a lesion after intramuscular injection [5].…”
Section: Introductionmentioning
confidence: 99%
“…A special electrophysiological technique has been developed and applied in a few case reports [5,6,8,9,11]. Although this technique is capable of confirming a lesion of the PFCN, it requires a specialized, meticulous technique [5].…”
Section: Discussionmentioning
confidence: 99%
“…Most reports of nerve injuries regarding the PFCN are caused by intramuscular injections, although there are also reports of injuries to the PFCN due to hematoma, tumor formation, prolonged cycling, falls on the ground, entrapment of the PFCN in the facia lata, abnormal venous formations, and compression of the nerve against the sciatic tuberosity [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%